Analysis of Income from Deep Coconut Farming and Farmers' Welfare Level in North Buton Regency - Hasrin; Iksan, Muhamad (Tarjih : Agribusiness Development Journal, 2024)
Family well-being refers to the conditions where a family's physical, material, mental, spiritual, and social needs are met, enabling them to lead a decent life within their environment. Coconut plants have high economic value as all parts of the plant can be utilized. North Buton holds significant potential for developing deep coconut plantations. However, coconut farmers in North Buton generally only produce copra and activated charcoal for sale, resulting in a limited contribution to increasing farmers' income and, consequently, their welfare. This study aims to analyze the income of coconut farming in North Buton and the level of farmers' welfare. The study sample consisted of 60 farmers selected through purposive sampling, who met the following criteria: they managed their own land, with at least 1 hectare, the coconut trees were productive, and they had been farming deep coconut for over 10 years. The results show that the average land area owned by farmers is 2 hectares, with an annual production of 22,891 coconuts. Farmers with 3.0-4.0 hectares of land had the highest income, averaging IDR 2,257,841 per month. Household income is allocated for food and non-food needs, with food consumption averaging IDR 1,163,000 per month and non-food consumption at IDR 1,530,000. Overall, the welfare level of deep coconut farmers' households in North Buton is categorized as prosperous, as the percentage spent on non-food needs exceeds that spent on food.